Peer relationship profiles in rural Chinese adolescents: Longitudinal relations with subjective well-being. (September 2021) - Chen, Yan; Wang, Liwei; Zhao, Jingxin
Using two waves of data, this study aimed to identify the peer relationship profiles of 1295 rural Chinese adolescents based on a person-centered approach and to examine the interactions among these profiles, left-behind status, and gender in predicting subsequent subjective well-being. Latent profile analyses identified four profiles: a socially competent profile, a socially accepted profile, an isolated profile, and a rejected profile. These profiles were linked to left-behind status (i.e. both-parent migration, father-only migration, mother-only migration, and non-parent migration) and gender. Moreover, left-behind status moderated the longitudinal relations between the peer relationship profiles and subjective well-being for boys and girls.